Predicting attendance of post treatment cancer care patients in general practice: the role of concomitant health conditions in the theory of planned behaviour - Ngune, Irene; Jiwa, Moyez; McManus, Alexandra; Hughes, Jeff; Parsons, Richard; Hodder, R. (WILEY-BLACKWELL, 2014)
Background: Due to the increasing numbers of patients at hospital cancer clinics, it is likely that specialist care of patients with colorectal cancer will need to be re-organised. More patients, who have been treated successfully, may need long-term support in primary care. Despite rigorous research work done in this field, uptake of this approach is rather slow. Issues that affect endorsement of this approach have not been fully determined and, in particular patient factors that may affect uptake of this programme have not been explored. Aim: To examine the role of comorbidities in the theory of planned behaviour (TPB) in influencing patients’ intention to attend follow-up visits with a general practitioner (GP). Methods: A self-administered questionnaire was developed based on the TPB to assess colorectal cancer (CRC) patients’ intention to attend follow-up visits with a GP. Results: Sixty-six patients participated in the study. All factors (attitude, subjective norms, and perceived behaviour control (PBC)) accounted for 43.3% of the variance on future follow-up visits. Attitude explained 23.3% of the variance, but PBC and subjective norms did not account for any significant variance (on future intention to attend a follow-up visit). Univariate analysis suggested that attitude and the presence of a coexisting chronic illness significantly affected future intention to visit a GP (attitude: R2 = 0.233, F [1, 65] = 4.345, p < 0.01; comorbidity: R2 = 0.128, F [1, 65] = 3.019, p < 0.05). Conclusions: Patients who believe their GP has the skills and knowledge to detect a recurrence and patients with other comorbidities are more likely to visit their GP following treatment.